Normalization of Microbiome after Diabetic Foot Ulcer Treatment. Issue 4 (16th October 2019) - Stephens, Sebastien; Stephens, Alexandre; Platt, Simon
Category: Diabetes Introduction/Purpose: Diabetic ulcers carry with it extensive morbidity. The microbiome of diabetic foot infections have previously been shown to be polymicrobial. We hypothesized that ulcer treatment would normalize the foot microbiome. Methods: Microbiome profiles of the fore, mid and hind diabetic foot. Diabetic foot (with ulcer) were taken pre and post treatment with a combination of surgical debridement, local and systemic antibiotics. 10 subjects were studied. Microbiome graphs and images pre and post treatment of feet are shown. Results: The microbiome profile of the diabetic foot almost completely normalized to that of normal flora. Before treatment, the foot microbiome was associated with polymicrobial pathogenic bacteria mostly away from the ulcer. The ulcer itself only contained minimal species, albeit pathogenic bacteria. The differences in profiles between the pre and post treatment were significantly different p < 0.01. Conclusion: Chicken or egg, the foot microbiome almost completely reverts to normal flora with simple ulcer debridement and local/systemic antibiotics. Our data point possibly suggest ulcers could be prevented by reducing pathogenic microbiome load (chlorhexidine washes) or microbiome transplants. We next move to controls as a proof of concept.